Correlation between White Globe Appearance and Clinicopathologic Characteristics in Early Gastric Cancer - Dae Jin Jung; Gwang Ha Kim; Kyungbin Kim; Hye Kyung Jeon; Dong Chan Joo; Moon Won Lee; Bong Eun Lee (Gut and Liver)
Background/Aims: Magnifying endoscopy with narrow-band imaging (ME-NBI) enables the visualization of detailed microsurface (MS) and microvascular (MV) structures in the gastrointestinal tract. White globe appearance (WGA) is a small whitish lesion with a globular shape identified during ME-NBI for early gastric cancer (EGC). This study aimed to investigate the associations between WGA, clinicopathological characteristics, and other ME-NBI findings in patients with EGC. Methods: The presence or absence of WGA in 122 patients (126 lesions) with an endoscopic diagnosis of EGC who underwent ME-NBI before endoscopic or surgical resection was prospectively collected and retrospectively analyzed. During ME-NBI, the MS and MV patterns and the presence of WGA and white opaque substances (WOS) were investigated. EGC cases were categorized as differentiated or undifferentiated type, and mucosal, submucosal, or advanced. Results: Of 126 lesions, WGA was observed in 25 (19.8%). WGA was associated with tumor size (≤2 cm [17/63, 27.0%] vs >2 cm [8/63, 12.7%]; p=0.044), histologic type (differentiated type [22/89, 24.7%] vs undifferentiated type [3/37. 8.1%]; p=0.033), and tumor location (upper third [1/11, 9.1%] vs middle third [18/58, 31.0%] and lower third [6/57, 10.5%]; p=0.017). Although WGA was observed more frequently in lesions with an oval/tubular MS pattern, a fine-network MV pattern, and the absence of WOS, the difference was not statistically significant (MS pattern, p=0.358; MV pattern, p=0.212; WOS, p=0.121, respectively). Conclusions: WGA was associated with small tumor size, differentiated-type histology, and middle-third tumor location, and was more frequently observed in lesions with an oval/tubular MS and fine-network MV patterns and the absence of WOS.